Systematic discovery of regulatory motifs in human promoters and 3′ UTRs by comparison of several mammals - Xie, Xiaohui; Lu, Jun; Kulbokas, E. J.; Golub, Todd R.; Mootha, Vamsi; Lindblad-Toh, Kerstin; Lander, Eric S.; Kellis, Manolis (Nature (London), 2005)
Comprehensive identification of all functional elements encoded in the human genome is a fundamental need in biomedical research. Here, we present a comparative analysis of the human, mouse, rat and dog genomes to create a systematic catalogue of common regulatory motifs in promoters and 3′ untranslated regions (3′ UTRs). The promoter analysis yields 174 candidate motifs, including most previously known transcription-factor binding sites and 105 new motifs. The 3′-UTR analysis yields 106 motifs likely to be involved in post-transcriptional regulation. Nearly one-half are associated with microRNAs (miRNAs), leading to the discovery of many new miRNA genes and their likely target genes. Our results suggest that previous estimates of the number of human miRNA genes were low, and that miRNAs regulate at least 20% of human genes. The overall results provide a systematic view of gene regulation in the human, which will be refined as additional mammalian genomes become available.